2011
DOI: 10.1186/bcr2865
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β represses Akt signaling in breast cancer cells via downregulation of HER2/HER3 and upregulation of PTEN: implications for tamoxifen sensitivity

Abstract: IntroductionThe inhibition of estrogen receptor (ER) α action with the ER antagonist tamoxifen is an established treatment in the majority of breast cancers. De novo or acquired resistance to this therapy is common. Expression of ERβ in breast tumors has been implicated as an indicator of tamoxifen sensitivity. The mechanisms behind this observation remain largely uncharacterized. In the present study, we investigated whether ERβ can modulate pathways implicated in endocrine resistance development.MethodsT47-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 51 publications
4
57
1
Order By: Relevance
“…GSK3␤ is active in resting cells through constitutive Tyr-216 phosphorylation, and PI3K/Akt-activating stimuli such as insulin can cause phosphorylation at Ser-9 and inactivation of GSK3␤ (8). The mechanism by which nongenomic activation of ER␤ might contribute to Ser-9 dephosphorylation and GSK3␤ activation in our study is still uncertain, but recent findings in rodent brain capillaries and breast cancer cells have shown that sustained ER␤ activation by extended exposure to estradiol resulted in PTEN activation and decreased GSK3 phosphorylation (19,27). Interestingly, part of the mechanism involved might also refer to the ER␤ response to Akt activation, as we demonstrated that activation of the PI3K/Akt pathway downregulated ER␤ degradation and activity in breast cancer cells (38).…”
Section: Discussionmentioning
confidence: 51%
“…GSK3␤ is active in resting cells through constitutive Tyr-216 phosphorylation, and PI3K/Akt-activating stimuli such as insulin can cause phosphorylation at Ser-9 and inactivation of GSK3␤ (8). The mechanism by which nongenomic activation of ER␤ might contribute to Ser-9 dephosphorylation and GSK3␤ activation in our study is still uncertain, but recent findings in rodent brain capillaries and breast cancer cells have shown that sustained ER␤ activation by extended exposure to estradiol resulted in PTEN activation and decreased GSK3 phosphorylation (19,27). Interestingly, part of the mechanism involved might also refer to the ER␤ response to Akt activation, as we demonstrated that activation of the PI3K/Akt pathway downregulated ER␤ degradation and activity in breast cancer cells (38).…”
Section: Discussionmentioning
confidence: 51%
“…35 We demonstrated that this effect occurs through a genomic action by performing transient transfection experiments with plasmid constructs containing progressively deleted regions in the 5'-flanking region of the PTEN promoter. Interestingly, the segment located between -1398 and -1118 from the transcription start 59 kDa, whereas two different Abs used in the evaluation of ERα expression did not show a 67 kDa signal, as reported for the classical ERα.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reason for the relative high endocrine resistance of ovarian cancer remains to be solved. In breast cancer, recent results suggested ERβ to be a predictive marker for good response to antiestrogens, although some contradictory data exist [6,[41][42][43][44][45][46]. In a recent study, we showed that long-time treatment with tamoxifen in vitro triggered endocrine resistance in ovarian cancer cells, an effect which was accompanied by ERβ downregulation, whereas expression of ERα or HER family kinases was not altered [17].…”
Section: Erβ In Ovarian Cancermentioning
confidence: 96%